Humanitarian status of the concept of “ecology” as the need for structuring its parts (Journal of Geography and Environmental Management, 2018)
The discrepancy between the name of science “ecology” and its content in the proclamation of this “new science” by E. Heckel in 1866 was noted., since the spatial concept inherent in the name(“oikos”) contradicts its content, designed primarily to study biological objects. This ambiguity to this day is one of the main reasons for the lack of a clear definition of the main attributes of environmentalscience – conceptual foundations, goals, tasks and content of this science, the subject and objects of its research, basic methods, methods of studying, etc. Moreover, in the diversity in the definition of ecology, proposed by various scientists, one of the most important issues of our time is often outside the frame of reference, concerning the creative or destructive impact on theenvironment of a specific representative of the biota, which is Homo sapiens. Now it is human activity that determines the main features of environmental science, which makes it attributed toone of the most unique concepts of the modernity, designed to canonize specific actions of man and humankind from the position of a conscious attitude to the environment. In this context, ecologyhas now «outgrown itself» and, with its new status, it responds not to a separate science, but to the universal idea, which must consider both the natural and humanitarian branches of humanknowledge. Accordingly, the concept of «ecology» now requires a new structuring, because the numerous variants of the classified division of the general ecology into «private sciences» do notcontribute to the ordering of the goals, objectives and content of these environmental units. To prevent the confusion of concepts and improve the overall systematics of the environment, it isproposed to distinguish between the ecology of natural content and the ecology of “man-made content”, conditionally calling the first supergroup “natural-or natural ecology”, and the second –“homogeneous or anthropogenic ecology”.